Pluralistic ignorance and social stigma - Stockley, Kieran (2023)
Pluralistic ignorance, a discrepancy between private beliefs and public understanding of these beliefs, is a social phenomenon which has been shown to have significant welfare consequences, but relatively little is understood about its origins. In this paper, we propose social stigma as a potential driver of pluralistic ignorance and design a survey structure intended to test for a relationship between this stigma and pluralistic ignorance across sociopolitical issues. As we are without results, we survey the literature and produce a short theoretical framework to motivate the research design, and also describe future directions for the research project.